Outcome of ultrasound guided reduction of intussusception in children by saline enema - Muqtadir, Ansari Mohammed Abdul; Gupta, Shweta Brajesh; Jadhav, Sarojini Pramod (International Surgery Journal, 2021)
Background: Intussuception is a common cause of acute intestinal obstruction in children and contributor of morbidity and mortality in children. The purpose of this study was to evaluate efficacy of hydrostatic reduction of intussusception over operative reduction using normal saline enema in children and to identify procedure related complications. Methods: All patients presenting to us with features of intussusception clinically and confirmed by ultrasonography between June 2015 to November 2017 were included in study. Depending on haemodynamic stability of patient and surgeon’s preference, patients were subjected to trial of hydrostatic reduction by normal saline enema or operative procedure. Patients with failure or partial reduction were taken for surgery. Results: The mean age was 21.07 months with a male preponderance. Of 53 patients attending the institute, 32 were given a trial of hydrostatic reduction which was successful in 28. Thus success rate was 87.5%. 1 patient succumbed resulting in 1.4% mortality rate after the procedure. It was observed that longer duration of symptoms reduced chances of reduction. 88%patients with successful hydrostatic reduction were discharged within 4 days of admission. Conclusions: We conclude that ultrasound guided saline enema is simple ,safe and effective method of treating intussusception in children with low rate of complications and can be strongly recommended as first line of treatment of intussusception in select group of paediatric patient, especially those reporting early to the hospital.